2001
DOI: 10.1109/50.939791
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and performance analysis of WDM transmission links employing semiconductor optical amplifiers

Abstract: Abstract-We theoretically explored the system limits of various single-and multichannel transmission links employing semiconductor optical amplifiers (SOAs). For this purpose, we developed an accurate model to describe the amplifier dynamics in the moderate and low saturation regimes. Our simulation results revealed the delicate balance among the level of saturation, the signal-tonoise ratio, and the amount of gain per amplifier required for optimum system performance. The modeling results have been confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…By careful adjustment of operation, SOAs are used for inline amplification of both single and multi channel systems. SOA has use as functional device in the area of long haul optical communication [1].…”
Section: Introductionmentioning
confidence: 99%
“…By careful adjustment of operation, SOAs are used for inline amplification of both single and multi channel systems. SOA has use as functional device in the area of long haul optical communication [1].…”
Section: Introductionmentioning
confidence: 99%
“…These practical advantages have rendered SOAs indispensable elements for performing a wide set of all-optical signal processing functions, as for example wavelength conversion, demultiplexing, regeneration, Boolean logic, detection and sampling [5][6][7], which are required in order to avoid the cumbersome and power-consuming optoelectronic conversions and fully benefit from the high transmission capacity of lightwave networks [8]. As a result of their increasingly important role, SOAs have attracted considerable theoretical interest and many studies have been conducted to explain their operation, predict their behavior and assist their design [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Especially, the results reported in [23] have been fundamental in describing pulse propagation and amplification through an SOA and understanding the physical mechanisms that govern this process.…”
Section: Introductionmentioning
confidence: 99%
“…[3] through observing its figures carefully. From this diagram, it can also be concluded that the gain asymmetry and shift of the SLA, which has been considered in wavelength conversion or WDM systems [7][8][9] and however is not, to our knowledge, included in investigating the temporal change of the pulse by the SLA, has an important influence on the rising and falling time.…”
Section: Resultsmentioning
confidence: 99%